Towards autonomic networking and selfconfigurating routers - Bullot, Thomas (2006)
IP Networks, and particularly the Internet, were proposed to be a simple and robust support for heterogeneous communications. This implies that only basic controls have to be done by network elements. Connection management, along with transport, and more generally communication management, has to be done by the terminals. For example, error detection mechanisms, error recovery mechanisms with “Slow Start”, are implemented within the transport protocol, managed by the terminals. However, integration of new services and increasing need for QoS require the network to be more and more flexible and adaptive. New algorithms and protocols are then proposed to address these issues, and include new configuration layers. Manual configuration of such network architectures is then very complex, if not impossible. We think that future core network elements will have to be more adaptive, but also more autonomic. Autoconfiguration is indeed a necessary condition to integrate new services in the network. We believe that autoconfiguration requires new knowledge provisioning and computing policies. This paper then presents an architecture of software agents, collaborative and autonomic. These agents are embedded inside the routers. Their role is to share local and situated knowledge, in order to control and optimize the existing control mechanism of the router.